User engagement in the development of a home-based virtual multidisciplinary stroke care clinic for stroke survivors and caregivers: a qualitative descriptive study. Issue 20 (25th September 2022) - Lam, Simon Kwun Yu; Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Siow, Elaine Kee Chen; Lee, Vivian Wing Yan; Shum, Edward Wai Ching; Lau, Alexander Yuk Lun
Abstract: Purpose: To understand the user expectations and the facilitators and barriers of using a virtual multidisciplinary stroke care clinic ("virtual clinic"). Methods: A qualitative descriptive study involving two rounds of face-to-face semi-structured interviews per participant was conducted. We purposively recruited ten participants in Hong Kong who were receiving traditional stroke rehabilitation. The first interview was conducted to explore participants' expectations. The second interview was conducted after a 4-week trial of the virtual clinic. Both interviews were analysed using thematic analysis. The findings were translated from Cantonese into English. Results: Before using the virtual clinic, the participants perceived a need for (i) information communication technology guidance and support, (ii) familiar hardware and applications, and (iii) services to meet psychosocial needs. Facilitators identified by the participants included (i) feeling safe and supported, (ii) willingness to learn, adapt to, and use the new service, and (iii) ease of use with a flexible schedule. Issues relating to (i) internet connectivity, (ii) hardware, and (iii) interface and design were perceived barriers to the use of the clinic. Conclusion: This study provides findings of users' expectations of using telehealth services. Their perspectives on facilitators and barriers may increase the adoption of the newly developed telehealth service. Implications for rehabilitation: To implement telehealth as part of post-stroke care, it is important to ensure that stroke survivors and caregivers have the necessary information and communication technology support and infrastructure to engage in two-way interactions. Stroke survivors and caregivers may be inclined to use telehealth services due to ease of use, having flexibility in scheduling consultation sessions, do not need to travel to the clinic, useful online content, and remote blood pressure monitoring. Addressing the barriers of using telehealth services (e.g., hardware issues, internet connectivity issues, and user interface to facilitate the reading of information on the website) can improve the usability and acceptance to ensure the successful adoption of telehealth as part of post-stroke recovery.